Professional practice models for nursing: A review of the literature and synthesis of key components - Slatyer, Susan; Coventry, L.; Twigg, D.; Davis, S. (Wiley-Blackwell Publishing Ltd., 2016)
This review aimed to synthesise literature describing the development and/or implementation and/or evaluation of a professional practice model to determine the key model components. A professional practice model depicts nursing values and defines the structures and processes that support nurses to control their own practice and to deliver quality care. A review of English language papers published up to August 2014 identified 51 articles that described 38 professional practice models. Articles were subjected to qualitative analysis to identify the concepts common to all professional practice models. Key elements of professional practice models were theoretical foundation and six common components: leadership; nurses' independent and collaborative practice; environment; nurse development and reward; research/innovation; and patient outcomes. A professional practice model provides the foundations for quality nursing practice. This review is an important resource for nurse leaders who seek to advance their organisation in a journey for excellence through the implementation of a professional practice model. This summary of published professional practice models provides a guide for nurse leaders who seek to develop a professional practice model. The essential elements of a professional practice model; theoretical foundation and six common components, are clearly described. These elements can provide the starting point for nurse leaders' discussions with staff to shape a professional practice model that is meaningful to direct care nurses.